Comorbid diseases as predictors of survival of primary total hip and knee replacements: a nationwide register-based study of 96 754 operations on patients with primary osteoarthritis. Issue 12 (19th December 2012) - Jämsen, Esa; Peltola, Mikko; Eskelinen, Antti; Lehto, Matti U K
Abstract : Objectives: To examine how comorbid diseases (cardiovascular diseases, hypertension, diabetes, cancer, pulmonary diseases, depression, psychotic disorders and neurodegenerative diseases) affect survival of hip and knee replacements. Methods: Data for this register-based study were collected by combining data from five nationwide health registers. 43 747 primary total hip and 53 007 primary total knee replacements performed for osteoarthritis were included. The independent effects of comorbid diseases on prosthesis survival were analysed using multivariate Cox regression analysis. Results: Occurrence of one or more of the diseases analysed was associated with poorer survival of hip (HR for revision 1.16, 95% CI 1.08 to 1.23) and knee replacements (1.23, 1.16 to 1.30). Cardiovascular diseases and psychotic disorders were associated with increased risk of revision after both hip (1.19, 1.06 to 1.34 and 1.41, 1.04 to 1.91, respectively) and knee replacement (1.29, 1.14 to 1.45 and 1.41, 1.07 to 1.86, respectively). Hypertension and diabetes were associated with early revision (0–5 years after primary operation) after knee replacements (1.14, 1.01 to 1.29 and 1.27, 1.08 to 1.50, respectively). Cancer was associated with poorer survival of hip replacements (1.27, 1.05 to 1.54) and late revision (>5 years) of knee replacements (2.21, 1.31 to 3.74). Depression affected the risk of early revision after hip replacement (1.50, 1.02 to 2.21). Neurodegenerative and pulmonary diseases did not affect prosthesis survival. Conclusions: Comorbid diseases may play an important role in predicting survival of primary hip and knee replacements. The mechanisms underlying these findings and their effect on cost-effectiveness of joint replacements, merit further research.